Belarus after Not Finished Transition - Folfas, Paweł; Czarny, Elżbieta; Menkes, Jerzy (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
In this article we search relationship between economic (also political) system and development opportunities of Belarus. We use interdisciplinary approach and analytical tools form economics, law and politics. The economy of Belarus, despite not finished transition, has been developing and strengthening relationships with abroad. However, at least a part of this success is connected with special economic and political ties with Russia.